2010
DOI: 10.1073/pnas.1016369107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a growth hormone-releasing hormone antagonist on telomerase activity, oxidative stress, longevity, and aging in mice

Abstract: Both deficiency and excess of growth hormone (GH) are associated with increased mortality and morbidity. GH replacement in otherwise healthy subjects leads to complications, whereas individuals with isolated GH deficiency such as Laron dwarfs show increased life span. Here, we determined the effects of treatment with the GH-releasing hormone (GHRH) receptor antagonist MZ-5-156 on aging in SAMP8 mice, a strain that develops with aging cognitive deficits and has a shortened life expectancy. Starting at age 10 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
0
34
1
1
Order By: Relevance
“…Considering that inhibition of GHRH, GH, and IGF-I in the current study reduced the antioxidant system in the liver, it is reasonable to postulate the antioxidative role of GHRH/GH/IGF-I axis in acute liver injury. Two previous studies showed that application of GHRH antagonist attenuated oxidative stress in human cancer cells and aging cognitive deficiency mice, respectively [35,36]. The inconsistency between the current study and these reports is probably from the differences between normal animal and cancer cell line, as well as the differences between the healthy and APAP-induced liver…”
Section: Discussioncontrasting
confidence: 54%
“…Considering that inhibition of GHRH, GH, and IGF-I in the current study reduced the antioxidant system in the liver, it is reasonable to postulate the antioxidative role of GHRH/GH/IGF-I axis in acute liver injury. Two previous studies showed that application of GHRH antagonist attenuated oxidative stress in human cancer cells and aging cognitive deficiency mice, respectively [35,36]. The inconsistency between the current study and these reports is probably from the differences between normal animal and cancer cell line, as well as the differences between the healthy and APAP-induced liver…”
Section: Discussioncontrasting
confidence: 54%
“…At present, resveratrol was reported to prevent early mortality in mice fed with a high-fat diet ) but failed to affect survival significantly in old mice (Miller et al 2011). A growth hormone releasing hormone antagonist has been shown to extend SAMP8 mice's median life span (Banks et al 2010), which was associated with decreased brain oxidative stress. Melatonin has also been reported to increase life span and longevity in SAMR1 and SAMP8 mice (Rodríguez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with earlier findings that GHRH-R antagonists suppress inflammation by reducing the production of inflammatory proteins, such as IL-β, NF-κB/p65, and COX-2, in experimental prostatic hyperplasia and breast cancer (15,18) and alleviate inflammation-triggered oxidative stress by increasing glutathione and decreasing glutathione peroxidase activity (29). The antagonist may alleviate inflammatory responses by acting as a local modulator for the maturation and migration of immune cells, including macrophages, lymphocytes, and other leukocytes (30)(31)(32). Because GH has been shown to target macrophages to trigger various immune responses (15), we argue that the GHRH-R antagonist may block the signaling of GHRH-R on the macrophages residing in the iris-CB and so inhibit synthesis and release of GH, resulting in reduced IGF1 secretion.…”
Section: Discussionmentioning
confidence: 99%